Tuning the electrical properties of graphene oxide through low-temperature thermal annealing. Issue 12 (7th March 2023) - Valentini, Cataldo; Montes-García, Verónica; Livio, Pietro Antonio; Chudziak, Tomasz; Raya, Jésus; Ciesielski, Artur; Samorì, Paolo
Abstract : The thermally-reduced graphene oxide (TrGO) obtained under air or inert atmosphere at relatively low temperatures (<300 °C) has been widely investigated as a scalable and low-cost method to produce materials featuring graphene-like characteristics. Abstract : During the last fifteen years, the reduction of electrically insulating graphene oxide (GO) through the elimination of oxygen containing functional groups and the restoration of sp 2 conjugation yielding its conducting form, known as reduced graphene oxide (rGO), has been widely investigated as a scalable and low-cost method to produce materials featuring graphene-like characteristics. Among various protocols, thermal annealing represents an attractive green approach compatible with industrial processes. However, the high temperatures typically required to accomplish this process are energetically demanding and are incompatible with the use of plastic substrates often desired for flexible electronics applications. Here, we report a systematic study on the low-temperature annealing of GO by optimizing different annealing conditions, i.e., temperature, time, and reduction atmosphere. We show that the reduction is accompanied by structural changes of GO, which affect its electrochemical performance when used as an electrode material in supercapacitors. We demonstrate that thermally-reduced GO (TrGO) obtained under air or inert atmosphere at relatively low temperatures (<300 °C) exhibits low film resistivities (10 −2 –10 −4 Ω m) combined with unaltered resistance after 2000 bending cycles when supported on plastic substrates. Moreover, it exhibits enhanced electrochemical characteristics with a specific capacitance of 208 F g −1 and a capacitance retention of >99% after 2000 cycles. The reported strategy is an important step forward toward the development of environmentally friendly TrGO for future electrical or electrochemical applications.